الحرب العراقية – الإيرانية 1980-1988 وانعكاساتها على الحركة الكردية في إيران - Jabbar Kate, Assist. Lect. Aqeel; Mufreh Daher, Prof. Dr. Mishal (Basra studies journal, 2025)
On September 22, 1980, Iraq launched a large-scale war against Iran, with former Iraqi President Saddam Hussein receiving substantial support from Arab and Western allies. Despite the ongoing conflict, the Iranian government remained resolute in its efforts to suppress the Kurdish uprising within its borders, which coincided with revolts by other non-Persian minorities. The Iranian leadership forged an alliance with the Iraqi Kurdistan Democratic Party, led by Masoud Barzani, who was based in Tehran. Under their agreement, the two parties collaborated against Iranian Kurds and Saddam Hussein’s regime, while also working to eliminate leftist elements within Barzani’s party. In exchange, Barzani received financial and military support on the condition that he refrains from interfering in Iranian Kurdistan. At the same time, Abdul Rahman Qassemlou, leader of the Iranian Kurdistan Democratic Party, offered to align his forces with the Iranian army during the war. However, the Iranian government rejected his proposal, as it was contingent upon granting national rights to Iranian Kurds. Instead, the government intensified its military operations to suppress the Kurdish insurgents, forcing them to retreat to rugged mountainous regions as the northern front of the war escalated. Between 1981 and 1987, Iranian Kurdish parties collaborated with the Iraqi regime in exchange for material support.